Increased inflammatory cytokines and oxidative stress enhanced antibody production in breast and prostate cancer patients with COVID-19 related depression - Binsaleh, Naif K.; Sherwani, Subuhi; Eltayeb, Reem; Qanash, Husam; Bazaid, Abdulrahman S.; Althobiti, Maryam; Hazzazi, Mohannad S.; Rajendrasozhan, Saravanan (Frontiers in Chemistry, 2023)
Cancer management is highly dependent on the immune status of the patient. During the COVID-19 pandemic, a large number of people suffered from anxiety and depression, especially cancer patients. The effect of depression on breast cancer (BC) and prostate cancer (PC) patients, during the pandemic has been analyzed in this study. Levels of proinflammatory cytokines (IFN-γ, TNF-α, and IL-6) and oxidative stress markers malondialdehyde (MDA) and carbonyl content (CC) were estimated in patients’ serum samples. Serum antibodies against in vitro hydroxyl radical (•OH) modified pDNA (•OH-pDNA-Abs) were estimated using direct binding and inhibition ELISA. Cancer patients showed increased levels of proinflammatory cytokines (IFN-γ, TNF-α, and IL-6) and oxidative stress markers (MDA and CC levels), which were further significantly enhanced in cancer patients with depression compared to normal healthy (NH) individuals. Increased levels of •OH-pDNA-Abs were detected in breast cancer (0.506 ± 0.063) and prostate cancer (0.441 ± 0.066) patients compared to NH subjects. These were found to be significantly elevated in BC patients with depression (BCD) 0.698 ± 0.078) and PC patients with depression (PCD) (0.636 ± 0.058). Inhibition ELISA also exhibited significantly high percent inhibition in BCD (68.8 ± 7.8%) and PCD (62.9 ± 8.3%) subjects compared to BC (48.9 ± 8.1%), and PC (43.4 ± 7.5%) subjects. Cancer is characterized by enhanced oxidative stress and increased inflammation, which may be exaggerated with COVID-19 related depression. High oxidative stress and compromised antioxidant homeostasis exerts alterations in DNA, leading to formation of neo-antigens, subsequently leading to the generation of antibodies. COVID-19 pandemic related depression needs to be addressed globally for improved cancer patient care and cancer disease management.